2008
DOI: 10.1080/00016480701387116
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results and prognostic factors in locally advanced hypopharyngeal cancer

Abstract: There was no significant difference in T and N status between the two treatment groups, nor were there significant differences in overall or disease-free survival or the incidence of distant metastasis (p >0.05). In the CCRT group and SRT group, the estimated 3-year overall survival was 39% and 44%, respectively. The SRT group had better local control than the CCRT group (p <0.05). Relatively, 27% patients retained their larynx function for more than 2 years in the CCRT group. Radiation doses >70 Gy yielded si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
3
22
1
Order By: Relevance
“…For local-regionally advanced hypopharyngeal tumors, 3y-DM free survival rates of as low as 30% are reported [8,17]. Comparisons of DM rates between the studies are difficult due to a wide range of treatment approaches, staging examinations, and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For local-regionally advanced hypopharyngeal tumors, 3y-DM free survival rates of as low as 30% are reported [8,17]. Comparisons of DM rates between the studies are difficult due to a wide range of treatment approaches, staging examinations, and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…More than three-quarters of patients afflicted with this cancer are at an advanced stage at the time of diagnosis (1). In the course of the disease, because of the early high rates of cervical lymph nodes metastasis (2), the overall survival is relatively poor, with 5-year survival rates <40%, despite aggressive surgical and adjuvant treatment (3,4). Smoking cigarettes and drinking alcohol are the main risk factors for HSCC (5).…”
Section: Introductionmentioning
confidence: 99%
“…Five-year OS rates ranging from 25 to 50% are usually published depending on the clinical characteristics of the patients and treatment modalities. Lee et al reported a 3-year OS rate of 39% in patients treated with concurrent RT + CT [16]. In patients treated by primary radical surgery or by larynx preservation-intended treatment, Chang et al showed 5-year OS rates of 47.4% and 18.6% for patients with stage III and IV hypopharynx cancer, respectively, without any significant difference according to the modality of treatment [15].…”
Section: Discussionmentioning
confidence: 95%